2016
DOI: 10.1039/c5cy01018g
|View full text |Cite
|
Sign up to set email alerts
|

First efficient catalyst recycling for the iridium-catalysed hydroformylation of 1-octene

Abstract: This paper describes the development of an efficient catalyst recycling concept for the iridium-catalysed hydroformylation of 1-octene through the investigation of biphasic systems, thermomorphic solvent systems and an ex situ extraction. Particularly high selectivities (>90%) towards the desired aldehydes as well as low rates of iridium leaching were observed using the monosulfonated triphenylphosphine ligand (TPPMS). In polar solvents such as propylene carbonate or N,N-dimethylformamide, low rates of catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…This atom-economic domino reaction, which starts with hydroformylation of alkenes and is followed by reductive amination, is an important and efficient synthesis of amines. [17] In our chosen exemplar reactionb etween cyclopentene and aniline (Scheme 4) with SulP1-MOF-808(Hf)-Rh (using [Rh-(acac)(CO) 2 ]a st he metal precursor), N-(cyclopentylmethyl)aniline was obtained in good yield (75 %).…”
Section: Resultsmentioning
confidence: 99%
“…This atom-economic domino reaction, which starts with hydroformylation of alkenes and is followed by reductive amination, is an important and efficient synthesis of amines. [17] In our chosen exemplar reactionb etween cyclopentene and aniline (Scheme 4) with SulP1-MOF-808(Hf)-Rh (using [Rh-(acac)(CO) 2 ]a st he metal precursor), N-(cyclopentylmethyl)aniline was obtained in good yield (75 %).…”
Section: Resultsmentioning
confidence: 99%
“…The screening reaction conditions, and 1 H NMR, 13 C NMR spectra for the products of hydroformylation of olefins. CCDC: Ir-L2, 1859529; Ir-L3, 2016248; Ir-L4, 2016247.…”
Section: Supporting Informationmentioning
confidence: 99%
“…In addition, Beller et al have shown that iridium, as an alternative metal to rhodium, can be used to prepare efficiently catalysts for the homogeneous hydroformylation of olefins. [10][11][12][13] It is well known that iridium-complex catalysts are often active for the hydrogenation of olefins. [14][15][16][17] Therefore an important issue to improve the performance of iridium-complexes for catalytic hydroformylation is to suppress the hydrogenation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behr group developed an efficient catalyst recycling concept by TMS system and an ex-situ extraction for hydroformylation of 1-octene by using iridium-catalyst (Scheme 7). [31] Very low iridium leaching (0.2 %) and good selectivities (> 90 %) towards the expected aldehydes were obtained with the monosulfonated triphenylphosphine ligand (TPPMS) in polar solvents like N,N-dimethylformamide or propylene carbonate. The catalyst was recycled for the five times with 0.2 % leaching and about 90 % conversion achieved.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%